The in vitro elution characteristics of vancomycin from the ligament augmentation and reconstruction system - Yong Luo; MingYang Zou; XinTao Zhang; SuFen Ye; XianCheng Huang; JiaTong Li; Tian You (Journal of Experimental Orthopaedics)
Abstract Purpose In this study, we aimed to characterize the elution profile of the ligament augmentation and reconstruction system (LARS) immersed in different concentrations of vancomycin using different immersion methods and determine whether the amount of vancomycin released was lower than the toxic concentrations for osteoblasts and chondroblasts. Methods The LARS was presoaked with 5, 2.5 or 1.25 mg/mL vancomycin solutions or wrapped in presoaked sterile gauze. After 10 min, the rinsed and unrinsed LARS samples were eluted in 100 mL agitated 37°C phosphate‐buffered saline. An ultraviolet spectrophotometer was used to analyze 1 mL samples taken after 10 min and 0.5, 1, 6, 12, 24h. Results Initially, no hysteresis was observed with vancomycin release into the solution at the tested conditions. The LARS elution profiles for different concentrations of the vancomycin solutions varied significantly. The amount of vancomycin released after 24 h was 9.10 ± 1.21, 5.29 ± 0.63 and 2.28 ± 0.59 mg for the 5, 2.5 and 1.25 mg/mL solutions, respectively. The amount of vancomycin released in the soaked group was significantly higher than in the rinsed and wrapped groups. The released amounts of vancomycin were below the toxic concentrations for osteoblasts and chondrocytes. Conclusion Soaked LARS can act as a reservoir for vancomycin, with the amount released and the elution profile dependent on rinsing, soaking solution concentration and soaking method. The eluted concentrations of vancomycin were lower than those previously reported for osteoblast and chondrocyte toxicity and higher than the minimal inhibitory concentrations for Staphylococci. Level of Evidence N/A.